The selection of SNMPTN applicants using the TOPSIS and rank order centroid (ROC) methods - Sutoyo, Muhammad Nurtanzis; Mangkona, Andi Tenri Sumpala (Prodi Teknik Informatika FIK Universitas Muslim Indonesia, 2021)
One of the main functions of higher education is to develop personality abilities and shape the character of a dignified nation's civilization. One of the entry pathways for new student admissions at State Universities is the SNMPTN Path. While the number of participants who are accepted by looking at the quota on the SNMPTN line is only 20 percent of the capacity. Decision Support System as a solution that can assist policymakers in determining a decision. In this study, a decision support system was built using the TOPSIS method for selecting and ROC as a weighting for each criterion. Based on the results of the selection test for SNMPTN participants using the TOPSIS and ROC methods as weighting, it proves that it can display the cumulative ranking results of each alternative based on the criteria values owned.